Translating genetic findings to epigenetics: identifying the mechanisms associated with aging after high-radiation exposure on earth and in space - Ruprecht, Nathan A.; Singhal, Sonalika; Sens, Donald; Singhal, Sandeep K. (Frontiers in Public Health, 2024)
Purpose: Exposure to radiation is a health concern both within and beyond the Earth's atmosphere for aircrew and astronauts for respective austere environments. The biological effects of radiation exposure from a multiomics standpoint is relatively unexplored and stands to shed light on tailored monitoring and treatment for those in these career fields. To establish a reference variable for genetic damage, biological age seems to be closely associated with the effect of radiation. Following a genetic-based study, this paper explores the epigenetic landscape of radiation exposure along with its associative effects to aging processes.We import the results of the genetics-based study that was secondary analysis on five publicly available datasets (noted as Data1). The overlap of these genes with new data involving methylation data from two datasets (noted as Data2) following similar secondary analysis procedures is the basis of this paper. We conduct standard statistical analysis on these datasets as well as supervised and unsupervised learning to create preranked gene lists that are used for functional analysis in Ingenuity Pathway Analysis.Results: There were 664 genes of interest from Data1 with 577 of which also found in Data2.There were 40 statistically significant methylation probes within 500 base pairs of the gene's transcription start sight and 10 of which within 100 base pairs which are discussed in depth.IPA yielded 21 significant pathways involving metabolism, cellular development, cell death, and diseases. Compared to gold standards for gestational age, we see relatively low error and standard deviation using newly identified biomarkers.From the various tests and analyses, we discuss 17 methylated genes that showed particular interest and potential in future studies. Common trends in oxidative stress, cell development, and metabolism continue our association between aging processes and effects of ionizing radiation exposure.